Potassium sodium niobate-based piezoelectric ceramics and preparation method and application thereof
By introducing Fe3+ into potassium niobate-based piezoelectric ceramics, defective dipoles are formed, and solid-phase preparation method is adopted, the problem of difficult to take into account both the piezoelectric performance and the temperature stability of the ceramics are achieved, and the high performance of the ceramics is achieved. Simplify the process.
Patent Information
- Application Number
- CN202310702030.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-14
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-06-14
AI Technical Summary
The piezoelectric properties and temperature stability of existing potassium niobate-based piezoelectric ceramics are difficult to take into account. Existing improvement methods such as preparing textured ceramics or keeping the phase transition temperature away from room temperature will lead to a decrease in the performance of the ceramics.
By introducing a specific ratio of Fe3+, a potassium sodium niobate-based piezoelectric ceramic with defective dipoles is formed, and a solid phase preparation method is used to simplify the process and improve the density and piezoelectric properties of the ceramic.
It achieves good piezoelectric properties and temperature stability of potassium niobate-based piezoelectric ceramics, while reducing the sintering temperature, simplifying the preparation process, and suitable for large-scale production.
Smart Images

Figure CN116715522B_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the research field of functional ceramic materials, and specifically relates to a potassium sodium niobate-based piezoelectric ceramic and a preparation method and application thereof. Background Art
[0002] Piezoelectric ceramics are a type of functional ceramics that have a significant impact on human production and life. In recent years, lead zirconate titanate (PZT)-based piezoelectric ceramics have been widely used due to their excellent piezoelectric properties, but PZT-based piezoelectric ceramics contain a large amount of lead, which is very harmful to the environment and human health. Potassium sodium niobate (KNN)-based lead-free piezoelectric ceramics have good piezoelectric properties and are environmentally friendly, and are expected to partially replace PZT-based piezoelectric ceramics, so they have attracted widespread attention from researchers.
[0003] The research results show that the piezoelectric properties of pure potassium sodium niobate ceramics are still far behind those of practical PZT ceramics. In order to improve the temperature stability of the piezoelectric properties of potassium sodium niobate-based piezoelectric ceramics, researchers have proposed many methods, such as preparing textured ceramics and keeping the phase transition temperature away from room temperature. However, the preparation of textured ceramics requires a complex process, and keeping the phase transition temperature away from room temperature inevitably reduces the piezoelectric properties of the ceramics. Summary of the invention
[0004] In view of the above problems existing in the prior art, the purpose of this application is to provide a potassium sodium niobate-based piezoelectric ceramic and its preparation method and application. The potassium sodium niobate-based piezoelectric ceramic of the present application has a simple preparation process, can ensure good piezoelectric performance, and has good temperature stability.
[0005] To achieve the above objectives, this application adopts the following technical solutions:
[0006] The present application provides a potassium sodium niobate-based piezoelectric ceramic, wherein the potassium sodium niobate-based piezoelectric ceramic has the following general formula: 0.45 Na 0.55 ) 0.98 Li 0.02 (Nb 0.77 Ta 0.18 Sb 0.05 )O3-x%Fe2O3, where x% is Fe2O3 (K 0.45 Na 0.55 ) 0.98 Li 0.02 (Nb 0.77 Ta 0.18 Sb 0.05 )O3 molar percentage, 0 <x<0.5。
[0007] In one embodiment, 0 <x≤0.3。
[0008] In one embodiment, the potassium sodium niobate-based piezoelectric ceramic has one or more of the following features:
[0009] (1) The piezoelectric constant d of the potassium sodium niobate-based piezoelectric ceramic 33 The range is 260pC / N~350pC / N;
[0010] (2) The electromechanical coupling coefficient Kp of the potassium sodium niobate-based piezoelectric ceramic is in the range of 0.35 to 0.50.
[0011] The present application also provides a method for preparing the potassium sodium niobate-based piezoelectric ceramic described in any of the above embodiments, comprising:
[0012] According to the general formula (K 0.45 Na 0.55 ) 0.98 Li 0.02 (Nb 0.77 Ta 0.18 Sb 0.05 )O3-x%Fe2O3 weigh out the raw material components and adopt the solid phase method to prepare the potassium sodium niobate based piezoelectric ceramic.
[0013] In one embodiment, the steps of preparing the potassium sodium niobate-based piezoelectric ceramic by a solid phase method include:
[0014] ball-milling and mixing the raw material components to prepare a wet slurry;
[0015] Drying, screening and preliminarily sintering the wet slurry to prepare a pre-sintered dry material;
[0016] ball-milling, drying and sieving the pre-sintered dry material to prepare ceramic powder;
[0017] Adding a binder to the ceramic powder, drying, grinding and then pressing into shape to prepare a ceramic embryo;
[0018] The potassium sodium niobate-based piezoelectric ceramic is obtained by sintering the ceramic body again, treating it with silver and polarizing it.
[0019] In one embodiment, in the steps of ball milling the raw material components and ball milling the pre-sintered dry material, the process parameters of the ball milling include:
[0020] The mass ratio of the raw material components or the pre-sintered dry material, the mixed ball and the ball milling medium is 1: (7-9): (4-6), and the ball milling is performed at a rotation speed of 300 rpm to 600 rpm for 8 hours to 15 hours;
[0021] The mixing beads include first ball milling beads and second ball milling beads in a mass ratio of 1:(1-3);
[0022] The diameter of the first ball milling beads is 3 mm to 8 mm, and the diameter of the second ball milling beads is 1 mm to 3 mm.
[0023] In one embodiment, the process parameters of the primary sintering include:
[0024] The temperature is set to 850℃~900℃ and the insulation time is 5h~7h.
[0025] In one of the embodiments, the mass ratio of the ceramic powder to the binder is (9-11):(2-4), and the binder is a polyvinyl alcohol solution with a mass fraction of 3% to 4%.
[0026] In one embodiment, the method for preparing the potassium sodium niobate-based piezoelectric ceramic has one or more of the following characteristics:
[0027] (1) The process parameters of the re-sintering include: a sintering temperature of 1070° C. to 1140° C. and a holding time of 2 h to 8 h;
[0028] (2) The silver-treated process parameters include: a holding temperature of 750° C. to 780° C. and a holding time of 20 min to 30 min;
[0029] (3) The polarization process parameters include: polarization temperature of 20°C to 50°C, polarization time of 20min to 40min, and polarization electric field of 2kV / mm to 4kV / mm.
[0030] The present application also provides an electronic device, comprising the potassium sodium niobate-based piezoelectric ceramic described in any of the above embodiments.
[0031] The potassium sodium niobate-based piezoelectric ceramic provided in this application introduces a specific proportion of Fe 3+ , making Fe 3+ The potassium sodium niobate-based piezoelectric ceramics formed with defective dipoles in combination with oxygen vacancies can have a higher Curie temperature and good temperature stability; at the same time, the piezoelectric ceramics of the present application have a larger piezoelectric coupling constant kp and mechanical quality factor Q m , and it can be used as a sintering aid to reduce the temperature of ordinary sintering and improve the density of ceramics; the potassium sodium niobate-based piezoelectric ceramics of the present application can be prepared through industrial raw materials and are easy to achieve large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 X-ray diffraction patterns of potassium sodium niobate-based piezoelectric ceramic discs prepared by sintering in Examples 1 to 3 and Comparative Example 1;
[0033] Figure 2The dielectric temperature spectrum of the potassium sodium niobate-based piezoelectric ceramic discs prepared by sintering in Example 3 and Comparative Example 1;
[0034] Figure 3 The hysteresis loop of the potassium sodium niobate-based piezoelectric ceramic disc prepared by sintering in Example 3 and Comparative Example 1;
[0035] Figure 4 This is the element mapping diagram of the potassium sodium niobate-based piezoelectric ceramic disc prepared by sintering in Example 3. DETAILED DESCRIPTION
[0036] The potassium sodium niobate-based piezoelectric ceramics of the present invention and their preparation methods and applications are further described in detail below in conjunction with specific embodiments. The present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive. Of course, they are merely examples and are not intended to limit the present application.
[0037] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application. Unless otherwise specified or there is a contradiction, the terms or phrases used herein have the following meanings:
[0038] In this application, the piezoelectric constant d 33 " is one of the most commonly used important parameters to characterize the performance of piezoelectric materials. Generally, the higher the piezoelectric constant of a ceramic is, the better the piezoelectric performance is. The first number in the subscript refers to the direction of the electric field, and the second number refers to the direction of stress or strain. "33" means that the polarization direction is the same as the direction of the force applied during measurement.
[0039] In this application, "electromechanical coupling coefficient" means that the piezoelectric vibrator converts mechanical energy into electrical energy, or converts electrical energy into mechanical energy during vibration. This parameter that represents the degree of mutual conversion between mechanical energy and electrical energy in the piezoelectric body is called the electromechanical coupling coefficient, which is a comprehensive physical quantity to measure the quality of piezoelectric conversion performance. Planar electromechanical coupling coefficient K p , reflecting the parameters of the electromechanical coupling effect of the thin disc when it is polarized and electrically excited along the thickness direction and undergoes radial stretching vibration.
[0040] The present application provides a potassium sodium niobate-based piezoelectric ceramic, wherein the potassium sodium niobate-based piezoelectric ceramic has the following general formula: 0.45 Na 0.55 ) 0.98 Li 0.02 (Nb 0.77 Ta 0.18 Sb0.05 )O3-x%Fe2O3, where x % is Fe2O3 (K 0.45 Na 0.55 ) 0.98 Li 0.02 (Nb 0.77 Ta 0.18 Sb 0.05 )O3 molar percentage, 0 <x<0.5。
[0041] Specifically, the value of x includes, but is not limited to, 0.05, 0.08, 0.09, 0.1, 0.15, 0.2, 0.25, 0.28, 0.29, 0.3, 0.31, 0.32, 0.35, 0.37, 0.38, 0.39, 0.4, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47 or 0.48.
[0042] This application can adjust (K by adjusting x 0.45 Na 0.55 ) 0.98 Li 0.02 (Nb 0.77 Ta 0.18 Sb 0.05 )The ratio of Fe2O3 to Fe2O3 increases the residual polarization intensity of the potassium sodium niobate-based piezoelectric ceramic, makes its polarization more complete, and improves the piezoelectric properties of the potassium sodium niobate-based piezoelectric ceramic.
[0043] In one example, 0 <x≤0.3。
[0044] In one example, the piezoelectric constant d of the potassium sodium niobate-based piezoelectric ceramic is 33 The range is 260pC / N~350pC / N.
[0045] In one example, the electromechanical coupling coefficient Kp of the potassium sodium niobate-based piezoelectric ceramic is in the range of 0.35 to 0.50.
[0046] In one example, the mechanical quality factor Q of the potassium sodium niobate-based piezoelectric ceramic is m The range is 45 to 80.
[0047] The present application also provides a method for preparing the potassium sodium niobate-based piezoelectric ceramic described in any of the above examples, comprising:
[0048] According to the general formula (K 0.45 Na 0.55 ) 0.98 Li 0.02 (Nb 0.77 Ta 0.18 Sb0.05 )O3-x%Fe2O3 weigh out the raw material components and adopt the solid phase method to prepare the potassium sodium niobate based piezoelectric ceramic.
[0049] In one specific example, the raw material components include K2CO3, Na2CO3, Nb2O5, Sb2O3, Li2CO3, Ta2O5 and Fe2O3.
[0050] Specifically, the potassium sodium niobate-based piezoelectric ceramics can be effectively synthesized by using K2CO3, Na2CO3, Nb2O5, Sb2O3, Li2CO3, Ta2O5 and Fe2O3 as raw materials. It is understandable that other carbonates, nitrates and oxides containing the above compound elements can also be used as raw materials to prepare the potassium sodium niobate-based piezoelectric ceramics.
[0051] In one example, the steps of preparing the potassium sodium niobate-based piezoelectric ceramic by a solid phase method include:
[0052] ball-milling and mixing the raw material components to prepare a wet slurry;
[0053] Drying, screening and preliminarily sintering the wet slurry to prepare a pre-sintered dry material;
[0054] ball-milling, drying and sieving the pre-sintered dry material to prepare ceramic powder;
[0055] Adding a binder to the ceramic powder, drying, grinding and then pressing into shape to prepare a ceramic embryo;
[0056] The ceramic body is sintered again, treated with silver, and polarized to prepare the potassium sodium niobate-based piezoelectric ceramic.
[0057] In one example, the drying step is performed in an oven, and specifically, the temperature of the oven is set to 80° C. to 90° C. It is understandable that in other examples, other devices may be used for drying.
[0058] In one example, in the steps of ball milling the raw material components and ball milling the pre-sintered dry material, the process parameters of the ball milling include:
[0059] The mass ratio of the raw material component or the pre-sintered dry material: the mixing ball: the ball milling medium is 1: (7-9): (4-6), and the ball milling is performed at a rotation speed of 300 rpm to 600 rpm for 8 hours to 15 hours;
[0060] The mixing beads include first milling beads and second milling beads in a mass ratio of 1:(1-3),
[0061] The diameter of the first ball milling beads is 3 mm to 8 mm, and the diameter of the second ball milling beads is 1 mm to 3 mm.
[0062] In one example, the equipment used in the ball milling step is a planetary ball mill. It is understandable that other ball mills that can ball mill the raw materials can be used.
[0063] In one specific example, the ball milling step uses anhydrous ethanol as the ball milling medium, and mixes the balls at a mass ratio of 1:2 of 5mm diameter: 2mm zirconia balls, so that the raw material components or pre-sintered dry materials: mixed balls: anhydrous ethanol have a mass ratio of 1:8:5, and the balls are milled at a speed of 400rpm for 8h to 15h. Specifically, the ball milling beads used in this application, which use a mixture of 5mm diameter and 2mm diameter zirconia balls as ball milling beads, have the best effect, and can grind the powder more evenly, which is beneficial to the complete performance and improvement of the material's performance. As a result, the potassium sodium niobate-based piezoelectric ceramics prepared in this application have very dense grains and no pores.
[0064] In one example, the process parameters of the primary sintering include:
[0065] The temperature is set at 850°C to 900°C and the holding time is 5h to 7h for the initial sintering.
[0066] In one example, the mass ratio of the ceramic powder to the adhesive is (9-11):(2-4), and the adhesive is a polyvinyl alcohol solution with a mass fraction of 3% to 4%.
[0067] In one example, the pressing process parameters include: using a mold to press the ground ceramic powder into a diameter of 10mm to 14mm and a thickness of 0.2mm to 2mm, and then sending it into a tubular furnace and keeping it at 600℃ to 700℃ for 1h to 2h to debind and prepare a ceramic embryo.
[0068] In one example, the debinding step is performed in a tube furnace. Specifically, the tube furnace is heated at a rate of 3°C / min to 5°C / min. It is understood that in other examples, other thermal processing devices can be used for debinding.
[0069] In one example, the process parameters of the re-sintering include: a sintering temperature of 1070° C. to 1140° C. and a holding time of 2 h to 8 h.
[0070] In one example, the process parameters of the silver treatment include: a holding temperature of 750° C. to 780° C. and a holding time of 20 min to 30 min.
[0071] In one example, the polarization process parameters include: a polarization temperature of 20° C. to 50° C., a polarization time of 20 min to 40 min, and a polarization electric field of 2 kV / mm to 4 kV / mm.
[0072] In one example, the polarization process needs to be performed in an insulating coal medium.
[0073] In one specific example, the insulating coal material is silicone oil.
[0074] In one example, the sintering step is performed in a muffle furnace. Specifically, the muffle furnace is heated at a rate of 3°C / min to 5°C / min. It is understood that in other examples, other thermal processing devices can be used for sintering.
[0075] The preparation method of potassium sodium niobate-based piezoelectric ceramics provided in the present application utilizes non-toxic and harmless industrial raw materials and is prepared by a traditional solid-phase sintering method. The sintering temperature is low and easy to achieve, and the preparation process is mature and simple, and can be used for large-scale industrial production.
[0076] Preferably, the method for preparing the potassium sodium acid-based piezoelectric ceramic provided in the present application comprises the following steps:
[0077] (1) Weigh: according to (K 0.45 Na 0.55 ) 0.98 Li 0.02 (Nb 0.77 Ta 0.18 Sb 0.05 )O3-x%Fe2O3 general formula: weigh the raw materials and put them into an oven and bake them at 200℃~250℃ for 2h~5h;
[0078] (2) ball milling: the raw materials are placed in a ball milling jar, anhydrous ethanol is used as a ball milling medium, and the raw materials are placed in a planetary ball mill together with zirconia beads with a diameter of 5 mm and 2 mm in a mass ratio of 1:(1-3) to make the mass ratio of the raw material component: mixed ball beads: ball milling medium be 1:(7-9):(4-6), and the ball milling is carried out at a rotation speed of 300 rpm to 600 rpm for 8 h to 15 h to prepare a wet slurry;
[0079] (3) Primary sintering: The wet slurry is sent to an oven for drying, sieved, and then sent to a box-type muffle furnace for primary sintering at 850° C. to 900° C. for 6 h to prepare a pre-sintered dry material;
[0080] (4) ball milling: the pre-sintered dry material is placed in a ball milling jar, anhydrous ethanol is used as a ball milling medium, and the pre-sintered dry material is placed in a planetary ball mill for ball milling together with zirconia beads with a diameter of 5 mm and 2 mm in a mass ratio of 1:(1-3), so that the mass ratio of the pre-sintered dry material: mixed ball beads: ball milling medium is 1:(7-9):(4-6), and the pre-sintered dry material is ball milled at a speed of 300 rpm to 600 rpm for 8 h to 15 h, and then sent to an oven for drying, and then ground through a 75-mesh sieve to prepare a ceramic powder;
[0081] (5) Granulation: Add 3% to 4% by mass of polyvinyl alcohol solution to the ceramic powder, place in an oven for drying, and grind through a 75-mesh sieve after drying;
[0082] (6) Pressing and molding: After screening, the ceramic powder is pressed into a ceramic body with a diameter of 12 mm and a thickness of 1 mm using a mold, and then sent into a tubular furnace and kept at 600° C. to 700° C. for 1 h to 2 h for debinding to prepare a ceramic body;
[0083] (7) sintering again: placing the ceramic body into a box-type muffle furnace and setting the temperature to 1070° C. to 1140° C. for 2 h to 8 h to prepare a ceramic product;
[0084] (8) Silver treatment: Silver paste is applied to the upper and lower surfaces of the re-sintered ceramic product at a holding temperature of 750°C to 780°C for 20min to 30min;
[0085] (9) Polarization: The ceramic product treated with silver is polarized by immersing in silicone oil for 20 min to 40 min at room temperature with a polarization electric field of 2 kV / mm to 4 kV / mm to prepare the potassium sodium niobate-based piezoelectric ceramic.
[0086] The present application also provides an electronic device, comprising the potassium sodium niobate-based piezoelectric ceramic described in any of the above embodiments.
[0087] The above-mentioned electronic equipment includes the above-mentioned potassium sodium niobate-based piezoelectric ceramics. The potassium sodium niobate-based piezoelectric ceramics have excellent piezoelectric properties, high Curie temperature, and good temperature stability. They can be used in drivers or sensors and are of great significance in the process of replacing lead-based piezoelectric ceramics in the future.
[0088] It is understandable that the present application does not limit the type of electronic equipment, which includes but is not limited to ultrasonic transducers, hydroacoustic transducers, electroacoustic transducers, ceramic filters, ceramic transformers, ceramic frequency discriminators, high-voltage generators, infrared detectors, surface acoustic wave devices, electro-optical devices, ignition and detonation devices, or piezoelectric gyroscopes.
[0089] In order to make the purpose and advantages of the present invention clearer, the potassium sodium niobate-based piezoelectric ceramics and the preparation method thereof of the present invention are further described in detail in combination with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and shall not be used to limit the present invention. The following embodiments do not include other components except for unavoidable impurities unless otherwise specified. The drugs and instruments used in the embodiments are conventionally selected in the art unless otherwise specified. The experimental methods for which specific conditions are not specified in the embodiments are implemented according to conventional conditions, such as the conditions described in the literature and books or the methods recommended by the manufacturer.
[0090] Example 1
[0091] Example 1 provides a potassium sodium niobate-based piezoelectric ceramic material and a preparation method thereof.
[0092] (1) Calculation: Using K2CO3, Na2CO3, Nb2O5, Sb2O3, Li2CO3, Ta2O5, and Fe2O3 as raw materials, according to the chemical formula (K 0.45 Na 0.55 ) 0.98 Li 0.02 (Nb 0.77 Ta 0.18 Sb 0.05 )O3-x%Fe2O3, x=0.4 Calculate the mass of each raw material required;
[0093] (2) Preparation: K2CO3 and Na2CO3 were placed in an oven at 220°C for 2 h to dry to remove moisture, and then the calculated raw material mass was weighed and placed in a ball mill, anhydrous ethanol was used as the ball milling medium, and zirconia beads with a mass ratio of 1:2 and a diameter of 5 mm and a diameter of 2 mm were mixed as ball milling beads, and the mass ratio of raw materials: ball milling beads: anhydrous ethanol was 1:8:4. The initial ball milling was carried out in a planetary ball mill at a speed of 400 rpm for 15 h to obtain a wet slurry;
[0094] (3) Primary sintering: The obtained slurry is placed in an oven and baked at 80°C for 6-8 hours to obtain dry powder, which is then placed in a crucible and pressed tightly. The crucible is covered and placed in a box-type muffle furnace at 900°C with a heating rate of 5°C / min for pre-sintering for 6 hours.
[0095] (4) Secondary ball milling: The pre-sintered block was crushed and the obtained powder was transferred into a ball milling jar. Anhydrous ethanol was used as the ball milling medium. Zirconia beads with a diameter of 5 mm and a diameter of 2 mm were mixed in a mass ratio of 1:2 for the second ball milling. The mass ratio of raw material: ball milling beads: anhydrous ethanol was 1:8:4. The ball milling was carried out in a planetary ball mill at a speed of 400 rpm for 15 h.
[0096] (5) Drying and sieving: The slurry obtained by ball milling is placed in an oven at 80°C for drying, and the dried powder is ground and passed through a 75-mesh sieve to obtain a powder with finer particle size and uniform particles;
[0097] (6) Granulation: Add 3% to 4% by mass of polyvinyl alcohol solution to the powder obtained by grinding and sieving, with the mass ratio of powder to polyvinyl alcohol solution being 10:3, mix the powder and polyvinyl alcohol solution evenly, put them into an oven at 80°C for 10 minutes to dry the moisture, grind them and pass them through a 75-mesh sieve;
[0098] (7) Pressing and molding: The powder obtained after the sieving process is pressed and molded using a mold to obtain a disc-shaped ceramic green body with a diameter of about 12 mm and a thickness of about 1 mm;
[0099] (8) Ordinary sintering: The obtained ceramic green body is placed in a tubular furnace at 650°C, with a heating rate of 3°C / min, and fired for 2 h to perform debinding treatment. The ceramic green body obtained after debinding is placed in a tubular furnace and kept at 1080°C for 4 h to obtain a ceramic finished product;
[0100] (9) Ceramic polarization: The finished ceramic product is treated with silver and kept at 780°C for 30 minutes. The ceramic with silver electrode is polarized in silicone oil at room temperature for 30 minutes with a polarization electric field of 3 kV / mm. After polarization, it is placed for 24 hours before performance testing.
[0101] Example 2
[0102] Example 2 is basically the same as Example 1, with the main difference being that the common sintering temperature in step (8) is 1090° C. The remaining preparation steps are consistent with the preparation method described in Example 1.
[0103] Example 3
[0104] Example 3 is basically the same as Example 1, with the main difference being that the common sintering temperature in step (8) is 1100° C. The remaining preparation steps are consistent with the preparation method described in Example 1.
[0105] Example 4
[0106] Example 4 is basically the same as Example 1, except that the chemical formula of the potassium sodium niobate-based piezoelectric ceramic material in step (1) is: 0.45 Na 0.55 ) 0.98 Li 0.02 (Nb 0.77 Ta 0.18 Sb 0.05 )O3-x%Fe2O3, x=0.3. The remaining preparation steps are consistent with the preparation method described in Example 1.
[0107] Comparative Example 1
[0108] Comparative Example 1 is basically the same as Example 1, except that the chemical formula of the potassium sodium niobate-based piezoelectric ceramic material is: 0.45 Na 0.55 ) 0.98 Li 0.02 (Nb 0.77 Ta 0.18 Sb 0.05 )O3-x%Fe2O3, x=0, wherein the common sintering temperature of step (8) is 1135° C. The remaining preparation steps are consistent with the preparation method described in Example 1.
[0109] Comparative Example 2
[0110] Comparative Example 2 is basically the same as Example 1, except that the chemical formula of the potassium sodium niobate-based piezoelectric ceramic material is: 0.45 Na 0.55 ) 0.98 Li 0.02 (Nb 0.81 Ta 0.18 Sb 0.01 )O3-0.4%Fe2O3.
[0111] Comparative Example 3
[0112] Comparative Example 3 is basically the same as Example 1, except that the chemical formula of the potassium sodium niobate-based piezoelectric ceramic material in step (1) is: 0.45 Na 0.55 ) 0.98 Li 0.02 (Nb 0.77 Ta 0.18 Sb 0.05 )O3-x%Fe2O3, x=0.5. The remaining preparation steps are consistent with the preparation method described in Example 1.
[0113] Performance Testing
[0114] The structure and performance of the potassium sodium niobate-based piezoelectric ceramic materials prepared in the examples and comparative examples were tested. The results are as follows: Figure 1 to Figure 4 And as shown in Table 1.
[0115] Table 1 d of Examples and Comparative Examples 33 , k p , Q m and density
[0116]
[0117] Table 1 shows the d of Examples 1 to 4 and Comparative Examples 1 to 3. 33 , k p, Q m and density. Through comparison, it is found that in Comparative Example 1, Fe2O3 is not included, and the piezoelectric constant d of the sodium potassium niobate-based piezoelectric ceramic material prepared 33 is low and the mechanical quality factor Q m < 45; in Comparative Example 2, by changing the molar ratio of Nb and Sb, the piezoelectric constant d of the sodium potassium niobate-based piezoelectric ceramic material prepared 33 , k p and Q m all decrease. In Comparative Example 3, when x is 0.5, although the value of the mechanical quality factor Q m increases, the piezoelectric constant d of the sodium potassium niobate-based piezoelectric ceramic material 33 , k p both decrease and cannot meet the actual application. It can be seen that when the molar fraction of Fe2O3 is selected in the range of 0 < x < 0.5, the sodium potassium niobate-based piezoelectric ceramic material can have a high Curie temperature d 33 , a large piezoelectric coupling constant kp and a mechanical quality factor Q m ; when the x value is too small, the piezoelectric constant d of the sodium potassium niobate-based piezoelectric ceramic material 33 and the mechanical quality factor Q m are low; when the x value is too large, the piezoelectric constant d of the sodium potassium niobate-based piezoelectric ceramic material 33 , k p are low and cannot meet the actual use. At the same time, by comparing Examples 1 to 3, it can be found that when the sintering temperature is 1100 °C, its performance is the best, the piezoelectric constant d 33 = 312 pC / N, k p = 0.48, Q m = 54, and the density is 4.77 g / cm 3 . By comparing Example 1 and Example 4, it can be found that although the d 33 and k p values in Example 4 decrease, but the d 33 value > 260 and the k p value > 0.35 can meet the actual use. At the same time, the mechanical quality factor Q of the sodium potassium niobate-based piezoelectric ceramic material in Example 4 m increases significantly.
[0118] Figure 1 For Examples 1 to 3 and Comparative Example 1 sintered and prepared Fe 3+X-ray diffraction spectrum of doped potassium sodium niobate-based piezoelectric ceramic discs. It can be seen from the figure that all example samples are perovskite structures without any impurity phases. When magnified and analyzed at 2θ=45.5°, double peaks coexist, and the left and right double peak peak intensity ratio is 1:2, indicating that the undoped Fe2O3 ceramic is a tetragonal phase, and the double peak intensity ratio of the Fe2O3-doped ceramic is 1:1, indicating that the doped ceramic is an orthorhombic phase and a tetragonal phase coexisting at room temperature. The coexistence of the two phases has a significant contribution to the improvement of the piezoelectric properties of KNNLTS ceramics, which is consistent with the results in Table 1.
[0119] Figure 2 The dielectric temperature spectra of the ceramic samples of Example 3 and Comparative Example 1 are shown in the figure. 3+ Doping and sintering aids can increase the orthorhombic-tetragonal phase transition temperature T O-T , T of KNNLTS ceramic in Comparative Example 1 O-T is about 25°C, while the T of KNNLTS-Fe ceramic in Example 3 is O-T When the temperature is raised to about 49°C, the phase transition temperature changes, resulting in a change in the phase structure of the KNNLTS-Fe ceramic in Example 3, which is basically consistent with the phase composition results determined by XRD of the ceramic. 3+ The dielectric peak of the doped piezoelectric ceramic material increases because the Fe 3+ Doping can create defect dipoles inside the material, generate excess space charges, and thus improve its piezoelectric properties.
[0120] Figure 3 The hysteresis loops of the potassium sodium niobate-based piezoelectric ceramic discs prepared by sintering in Example 3 and Comparative Example 1 were tested at 1 Hz. It was found that the larger the piezoelectric constant was, the larger the residual polarization intensity was, which was higher than that of the undoped Fe 3+ For values of , the curve is saturated and approximately rectangular. Figure 4 The element mapping diagram of the potassium sodium niobate-based piezoelectric ceramic disc prepared by sintering in Example 3 shows that the distribution of the elements in the KNNLTS-Fe ceramic in Example 3 is relatively uniform. The Li element is too light to be displayed on the mapping diagram. Although the content of the Fe element is very small, it can be seen from the mapping that the distribution is basically consistent with other elements.
[0121] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0122] The above-described embodiments only express several implementation methods of the present application, which is convenient for understanding the technical solution of the present application in detail, but it cannot be understood as limiting the scope of protection of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several variations and improvements can be made, which all belong to the protection scope of the present application. It should be understood that the technical solutions obtained by those skilled in the art through logical analysis, reasoning or limited experiments on the basis of the technical solutions provided in the present application are all within the protection scope of the claims attached to the present application. Therefore, the scope of protection of the patent of this application shall be based on the content of the attached claims, and the description can be used to interpret the content of the claims.
Claims
1. A potassium sodium niobate-based piezoelectric ceramic, characterized in that: The potassium sodium niobate-based piezoelectric ceramic has the following general formula: 0.45 Na 0.55 ) 0.98 Li 0.02 (Nb 0.77 Ta 0.18 Sb 0.05 )O3- x %Fe2O3, where x % is Fe2O3 (K 0.45 Na 0.55 ) 0.98 Li 0.02 (Nb 0.77 Ta 0.18 Sb 0.05 )O3 molar percentage, 0.3≤ x ≤0.4; The preparation steps of the potassium sodium niobate-based piezoelectric ceramic include: The raw material components are ball-milled and mixed to prepare a wet slurry; Drying, screening and preliminarily sintering the wet slurry to prepare a pre-sintered dry material; ball-milling, drying and sieving the pre-sintered dry material to prepare ceramic powder; Adding a binder to the ceramic powder, drying, grinding and then pressing into shape to prepare a ceramic embryo; The ceramic embryo body is sintered again, treated with silver and polarized to obtain the potassium sodium niobate-based piezoelectric ceramic; The process parameters of the ball milling include: the mass ratio of the raw material component or the pre-sintered dry material, the mixed ball and the ball milling medium is 1: (7-9): (4-6), and the ball milling is performed at a rotation speed of 300 rpm to 600 rpm for 8 h to 15 h; the mixed ball includes a first ball milling bead and a second ball milling bead in a mass ratio of 1: (1-3); the diameter of the first ball milling bead is 3 mm to 8 mm, and the diameter of the second ball milling bead is 1 mm to 3 mm; The process parameters of the primary sintering include: the temperature is set at 850°C to 900°C, and the holding time is 5h to 7h; The process parameters of the re-sintering include: a sintering temperature of 1070° C. to 1140° C. and a holding time of 2 h to 8 h.
2. The potassium sodium niobate-based piezoelectric ceramic according to claim 1, characterized in that: x =0.3 or 0.
4.
3. The potassium sodium niobate-based piezoelectric ceramic according to claim 1 or 2, characterized in that: The piezoelectric constant d of the potassium sodium niobate-based piezoelectric ceramic 33 The range is 260 pC / N~350 pC / N.
4. The potassium sodium niobate-based piezoelectric ceramic according to any one of claims 1 to 3, characterized in that: The electromechanical coupling coefficient K of the potassium sodium niobate-based piezoelectric ceramic p The range is 0.35~0.
50.
5. The method for preparing the potassium sodium niobate-based piezoelectric ceramic according to any one of claims 1 to 3, characterized in that: The process parameters of the silver treatment include: a holding temperature of 750° C. to 780° C. and a holding time of 20 min to 30 min.
6. The potassium sodium niobate-based piezoelectric ceramic according to any one of claims 1 to 3, characterized in that: The mass ratio of the ceramic powder to the adhesive is (9-11):(2-4), and the adhesive is a polyvinyl alcohol solution with a mass fraction of 3%-4%.
7. The potassium sodium niobate-based piezoelectric ceramic according to any one of claims 1 to 3, characterized in that: The polarization process parameters include: polarization temperature of 20°C to 50°C, polarization time of 20min to 40min, and polarization electric field of 2 kV / mm to 4 kV / mm.
8. A method for preparing the potassium sodium niobate-based piezoelectric ceramic according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) Weigh: according to (K 0.45 Na 0.55 ) 0.98 Li 0.02 (Nb 0.77 Ta 0.18 Sb 0.05 )O3- x %Fe2O3 General Formula Weigh the raw materials and put them into the oven for drying at 200℃~250℃ for 2h~5h; (2) Ball milling: Place the raw materials in a ball mill, use anhydrous ethanol as the ball milling medium, and 5 mm and 2 mm zirconia beads are placed together in a planetary ball mill in a mass ratio of 1:(1-3) for ball milling, so that the mass ratio of the raw material component: mixed ball beads: ball milling medium is 1:(7-9):(4-6), and the ball milling is performed at a rotation speed of 300 rpm-600 rpm for 8 h-15 h to prepare a wet slurry; (3) Primary sintering: The wet slurry is sent to an oven for drying, sieved, and then sent to a box-type muffle furnace for primary sintering at 850°C to 900°C for 6 h to prepare a pre-sintered dry material; (4) ball milling: the pre-sintered dry material is placed in a ball milling jar, anhydrous ethanol is used as a ball milling medium, and the pre-sintered dry material is placed in a planetary ball mill for ball milling together with 5 mm and 2 mm diameter zirconium oxide beads in a mass ratio of 1:(1-3) so that the mass ratio of the pre-sintered dry material: mixed ball beads: ball milling medium is 1:(7-9):(4-6), and the pre-sintered dry material is ball milled at a speed of 300 rpm-600 rpm for 8 h-15 h, and then sent to an oven for drying, and then ground through a 75-mesh sieve to prepare a ceramic powder; (5) Granulation: Add 3% to 4% by mass of polyvinyl alcohol solution to the ceramic powder, place in an oven for drying, and grind through a 75-mesh sieve after drying; (6) Pressing and molding: After screening, the ceramic powder is pressed into a ceramic body with a diameter of 12 mm and a thickness of 1 mm using a mold, and then sent into a tubular furnace and kept at 600°C~700°C for 1h~2h for debinding to prepare a ceramic body; (7) Sintering again: placing the ceramic body into a box-type muffle furnace and setting the temperature to 1070° C. to 1140° C. for 2 h to 8 h to prepare a ceramic product; (8) Silver treatment: Silver paste is applied to the upper and lower surfaces of the re-sintered ceramic product, and the insulation temperature is 750℃~780℃, and the insulation time is 20min~30min; (9) Polarization: The ceramic product treated with silver is polarized by immersing in silicone oil for 20 min to 40 min at room temperature with a polarization electric field of 2 kV / mm to 4 kV / mm to prepare the potassium sodium niobate-based piezoelectric ceramic.
9. An electronic device, characterized in that: The invention comprises the potassium sodium niobate-based piezoelectric ceramic according to any one of claims 1 to 7.